Efektivitas Layanan Darurat Jakarta Siaga 112 dalam Penanganan Kebakaran oleh UPT. Pusat Data & Informasi Kebencanaan BPBD Provinsi DKI Jakarta - Musa Musa (Jurnal Good Governance, 2020)
This research was conducted to determine the Effectiveness of Jakarta Siaga 112 Emergency Services in Fire Management by UPT. Disaster Data & Information Center of BPBD DKI Jakarta Province by paying attention to aspects contained in the Effectiveness of the Jakarta Siaga Emergency Service Program 112. The research method was carried out with a case study method with data collection techniques using interview methods and document review. Interviews were conducted on 10 (ten) key informants, document review focused on documents related to the Jakarta Emergency Alert Service 112 Effectiveness research in Fire Management. The results showed that the Effectiveness of Jakarta Siaga 112 Emergency Services in Fire Management by UPT. The Center for Disaster Data & Information BPBD DKI Jakarta Province Its effectiveness is still low, due to the Implementation of Emergency Services Jakarta Standby 112 in Fire Management implemented by UPT. Disaster Data & Information Center of BPBD DKI Jakarta Province in terms of the Target Group Understanding of the Program, the Achievement of the Program Objectives aspects, and the Program Follow-up aspects. It is recommended to continue to disseminate this Emergency Service to the public, it is necessary to increase the firm commitment of the Head of 8 SKPD related to fire management so that all units play a role in accordance with the Standard Operating Procedures (SOPs) for Fire Management and the evaluation and follow-up of program services that are held periodically 3 once a month.Keywords: Effectiveness, Emergency Services, Fire Handling